Peningkatan Kedisiplinan Siswa Menggunakan Layanan Konseling Kelompok Dengan Pendekatan REBT - Rahayu Ningtias, Listia; Juwita Zuraida, Dita; Sumitro, Ari (BULLET : Jurnal Multidisiplin Ilmu, 2023)
This research was conducted using a quantitative approach, a type of research quasi experimental design with the form of two experimental and control groups using pretest-posttest. This study involved grade XI students of As-Syafi'iyah 02 Bekasi Islamic High School. Based on the results of distributing questionnaires to grade XI students, it shows that students have problems in student discipline. The population of class XI is 145 and the sample used is 16 students divided into 8 control groups and 8 experimental groups. data analysis techniques using several stages, namely validity trials, reliability tests, normality tests, Homogeneity tests and T test hypotheses using SPSS for windows 23 version on paired t sample test analysis with experimental posttest results 000 <0.5 posttest control 000 <0.5. This shows that there is an increase in good discipline by using treatment or not doing treatment. It can be concluded that there is an influence between rational emotive behavior therapy group counseling services on increasing student discipline.